Is Distal Chronic Thromboembolic Pulmonary Hypertension Treatable with PAH Targeted Drugs? - Cannon, J. E.; Pepke-Zaba, J. (Seminars in Respiratory and Critical Care Medicine, 2013)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a life-threatening condition that historically has a poor outcome with supportive medical treatment. Pulmonary endarterectomy (PEA) is the treatment of choice and offers the only chance of cure. A significant proportion of patients is either not suitable due to the distal distribution of the disease or has persistent pulmonary hypertension (PH) after PEA. Despite the lack of licensed therapies for CTEPH, the similarities in pathobiology of pulmonary arterial hypertension (PAH) and CTEPH has led to the compassionate use of PAH therapies in CTEPH patients. This article reviews the pathobiology of CTEPH and summaries the available evidence for the use of PAH-targeted drugs in CTEPH.
Keywords: chronic thromboembolic pulmonary hypertension; bosentan; prostanoids; riociguat and sildenafil